Economic scenario of cellulase enzyme production using Palm Oil Mill Effluent (POME) - Karim, A.N. Mustafizul; Hamdan, Hamdan; Alam, Md Zahangir; Iqbal, M. (Trans Tech Publications Ltd., Switzerland, 2012)
This paper presents an analysis on the economic suitability of a large scale plant for the production of cellulase enzyme from Palm Oil Mill Effluent (POME). Based on the data and other relevant information gathered from indigenous operation of a lab and a pilot scale bio-reactors (30L and 300L capacities), a predicted evaluation of economic aspects of enzyme production with a 3000L bioreactor has been made. Factors such as the initial price and installation cost, the expenses for raw materials, operation and maintenance of the plant, overhead, utilities, logistics etc. were considered. Enzyme output from the proposed bioreactor was estimated depending on the optimum operational conditions established by the small scale investigation. Net present value (NPV) of the project was evaluated by using the discounted cash-flow analysis. With a conservative view of 5% escalation of recurring costs and a target of 70% capacity utilization an NPV of MYR 2,5 million was found to be achievable for a 10% discount rate and a plant life of 10 years,. Economic scenario developed for 50-100% range capacity utilization indicating the NPV can be helpful in making decisions for implementation of such plants. Thus production of cellulase enzyme from POME using a 3000L bioreactor is found to be economically attractive.